h - Funke, Carolin; Dijkzeul, Dennis; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
This open access book studies disability inclusion in humanitarian crises. It addresses the challenges of recognizing and including persons with disabilities and indicates the degree to which disability is being mainstreamed in international law and humanitarian action. Further, it explores how international organizations have promoted a rights-based understanding of disability in international law, and to what extent this understanding has gained acceptance in humanitarian policy and practice. Theoretically, Funke and Dijkzeul explore the robustness of the disability inclusion norm cluster during processes of institutionalization, translation, and implementation. The book examines these processes from a multi-level perspective, which involves a variety of actors beyond states, including organizations of persons with disabilities. Situating their analysis within the literature on humanitarian action and development, the authors argue for an increased focus on processes (3z(Bbelow(3y (Bthe international level in international relations and international law scholarship to better understand disability inclusion. Carolin Funke is an expert in disability inclusion and internal displacement. She currently works at TU Dortmund University and is research affiliate at the Refugee Law Initiative, University of London. Before, she was postdoctoral researcher at the Institute for International Law of Peace and Armed Conflict at Ruhr University Bochum and research fellow at the Institute of Security and Global Affairs, Leiden University. She has conducted extensive field research in Georgia and Cox$1 (Bs Bazar, Bangladesh. Her latest book (3z(BDurable Solutions: Challenges with Implementing Global Norms for Internally Displaced Persons in Georgia(3y (Bwas published in 2022. Dennis Dijkzeul is Professor of conflict and organization research at Ruhr University Bochum. He was the founding director of the Humanitarian Affairs Program at Columbia University in New York. He has conducted research on international and local organizations in the United States, Europe, DR Congo, Uganda, South Sudan, and Afghanistan. His latest books are (3z(BDiaspora Organizations in International Affairs(3y (B(2020, with Margit Fauser), and (3z(BInternational Organizations Revisited: Agency and Pathology in a Multipolar World(3y (B(2021, with Dirk Salomons).s
Chapter 1: Introduction -- Chapter 2: Background: Disability and Diversity in Humanitarian Action -- Chapter 3: Understanding Norms, Norm Clusters and Robustness at Different Levels of GlobalGovernance -- Chapter 4: Institutionalizing a New Understanding of Disability in Humanitarian Action at the International Level -- Chapter 5: Translating Disability Inclusion into the Humanitarian System -- Chapter 6: Implementing Disability Inclusion: Comparing Bangladesh and South Sudan -- Chapter 7: Analysis across Actors and Levels -- Chapter 8: Conclusions.
Keywords: Human body -- Social aspects; International relations; Human rights; Sociology of the Body; International Relations; Human Rights